AN ANNOTATED TRANSLATION OF MY LOVER, MY FRIEND - Suratni, Suratni (English Department FBS UNP, 2013)
This article is based on an annotated translation research. The object of the research is an English novel My Lover My Friend, written by Suprina Frazier. The purpose of this research are (1) to attain factual information concerning the problems faced by the researcher in translating the source text; (2) to give plausible solutions to the difficulties. In conducting this annotated translation research, the researcher involved the introspective and retrospective research. The result of the research covered two main point. First, the finding reveals that from the 25 difficult problems, six were words, seven were phrases, two were idioms, four were clauses, and six were sentences. However in this journal, the researcher took ten items to be annotated. Second, those difficulties were solved by referring to the relevant theories of translation and English-Indonesian languages.